An Explorative Study on the Implementation of E-HRM in CIMB Bank - Venkatesan, Vinod (2012)
As of the globalization era there has been many changes takes place which can be seen clearly in many aspects. This globalization takes place because of the Information Technology (IT) that is growing rapidly. The growth of the IT has lead people to change in a way of doing things more effective and efficient. Previously, in organization most of the things would be done manually and it is solely human based but now everything has changed where organization has moved on towards the IT application. A clear example can be seen in the banking industry where now everything has change to the E-banking system. This mean it can be done with the presence of internet connection even from any location. This advancement doesn’t stop just at the E-banking but it has the influence on the human resource management where E-HRM has been introduced. Basically, the need of HRM helps the organization in the way of meeting the wants and needs of the administration and the employee of the network organization. Considering this, the requirements for such a form of HRM that become apparent are: on-line applications for HR information, and the tools that are available at any time in any place, and that enable continuous interaction between the employees and the organization. The software industry has developed for the HR personal to make it able to store, sort and retrieve information placed on huge databases. E-HR is the actually a strategic initiative to make the organization propel itself from daily operational, monotonous requirements and making it more in tune with the decision making and better understanding of the employees.